A single-group trial of end-stage patients with anthroponotic cutaneous leishmaniasis: Levamisole in combination with Glucantime in field and laboratory models. (March 2019) - Bamorovat, Mehdi; Sharifi, Iraj; Fekri, Alireza; Keyhani, Alireza; Aflatoonian, Mohammad Reza; Heshmatkhah, Amireh; Oliaee, Razieh Tavakoli; Khosravi, Ahmad; Naderi, Afsaneh; Parizi, Maryam Hakimi; Mostafavi, Mahshid; Varma, Rajender S.
Abstract: Currently, there is no satisfactory treatment modality available for cutaneous leishmaniasis (CL). The major objective of the present study was to explore the effect of immunomodulator-levamisole in combination with Glucantime in end-stage unresponsive patients with anthroponotic CL (ACL). Twenty end-stage unresponsive patients with ACL were identified for participation in this single-group trial study. Simultaneously, each patient was received a combination of levamisole pills along with Glucantime during the remedy course. Several in vitro complementary experiments were performed to evaluate the mode of action of levamisole and Glucantime alone and in combination using a macrophage model, in vitro MTT assay, flow cytometry and quantitative real time PCR (qPCR). Overall, 75% of the patients showed complete clinical cure, 10% partially improved and the remaining (15%) had underlying chronic diseases demonstrated no response to the treatment regimen. In in vitro studies, there was no cytotoxic effect associated with these drugs in the range of our experiments. The findings by the flow cytometric analysis represented that the highest apoptotic values corresponded to the drugs combination (32.23%) at 200 μg/ml concentration. Finally, the gene expression level of IL-12 p40, iNOS and TNF-α promoted while the level of IL-10 and TGF-β genes reduced as anticipated. The findings clearly indicated that the combination of levamisole and Glucantime should be considered in end-stage unresponsive patients with ACL who have not responded to basic treatments. The immunomodulatory role of levamisole in mounting immune system as documented by the in vitro experiments and further substantiated by this single-group trail study was highlighted. Highlights: The effect of levamisole in combination with Glucantime in end-stage patients. Twenty end-stage patients with ACL were selected in this single-group trial study. Several in vitro complementary experiments were performed to evaluate of drugs. Overall, 75% of the end-stage patients showed complete clinical cure. Levamisole plus Glucantime should be considered in unresponsive patients with ACL.